1997
DOI: 10.1590/s0103-50531997000500009
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic removal of metals using a flow-through cell with a reticulated vitreous carbon cathode

Abstract: O objetivo do presente trabalho foi estabelecer um processo eletrolítico para remover metais de efluentes aquosos usando um catodo tridimensional de carbono vítreo reticulado. Durante o desenvolvimento do trabalho foi estudado a influência do fluxo do eletrólito e da porosidade do eletrodo. A célula eletrolítica utilizou potenciais tais que a reação de redução ocorreu sob controle de transporte de massa. A célula demonstrou eficiência na remoção de chumbo, zinco e cobre, reduzindo a concentração desses metais … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 16 publications
0
26
1
1
Order By: Relevance
“…for metal removal in waste water treatment [19][20][21] or electrochemical pre-concentration for atomic spectroscopy. 22 Obviously, the electrochemical properties such as electrochemical signal to background ratio are of no significance here.…”
Section: Resultsmentioning
confidence: 99%
“…for metal removal in waste water treatment [19][20][21] or electrochemical pre-concentration for atomic spectroscopy. 22 Obviously, the electrochemical properties such as electrochemical signal to background ratio are of no significance here.…”
Section: Resultsmentioning
confidence: 99%
“…8-10.The data were fitted to obtain the following correlation applied for different initial zinc concentrations: (5) For 13067 < Re < 57552 and 550 < Sc < 1390 with correlation coefficient (CR) equal to 0.98.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Other researchers calculate the diffusion coefficient of metallic ions in a dilute solutions under the conditions of their experiments using Levich equation. 3,6,8,10) The measurements of mass transfer coefficients to rotating disc electrode have been investigated by several researchers using different electrode materials and reactions systems under laminar, transient and turbulent flows.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear from equation 7, that Q has no significant influence on X Pb 2+ (see also Figure 3a), although several other studies showed that the rate of electrochemical reactions under mass transport conditions is dependent on Q. 2,3,6,12 According to Koene and Janssen, 32 increases in Q enhance the electrochemical-reaction rate as a consequence of the diffuse layer becoming thinner. In the present case, lower Q values possibly promoted insignificant changes in the mass transport coefficient, while higher ones led to the formation of preferential streaming channels and/or dead zones.…”
Section: Optimization Of Pb 2+ Removalmentioning
confidence: 98%
“…Electrochemical techniques have been extensively used for the treatment of aqueous effluents because they offer an environmentally and friendly way of removing toxic metallic ions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] and/or organic species [16][17][18][19][20][21][22] via redox reactions. The environmental compatibility is the main advantage of electrochemical methods, as the reagent, the electron, is a "clean reagent".…”
Section: Introductionmentioning
confidence: 99%